2010
DOI: 10.1136/ip.2010.029215.120
|View full text |Cite
|
Sign up to set email alerts
|

Driving behaviour, driver style and road traffic accidents among young medical group

Abstract: Road traffic accidents (RTAs) are increasingly being recognised as a growing public health problem. In Egypt, RTAs constitute 45% of all injury mortalities. The main objective of the study was to identify the driving style and driving behaviour of medical students and its association with car accident involvement. Driving style and behaviour of 450 medical students were reported using a self administered questionnaire. Driving style included: driving with excessive speed, deviance, calmness, planning and conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 6 publications
0
14
0
3
Order By: Relevance
“…Males are more likely to adopt risky driving behaviours and to be involved in car crashes than their female counterparts [6]. The factors associated with RTA's in the country are comparable to what one would expect in most countries, although a further breakdown of factors under 'other' categories is necessary since that particular category has over half the number of accidents.…”
Section: Road Traffic Accidentsmentioning
confidence: 69%
See 2 more Smart Citations
“…Males are more likely to adopt risky driving behaviours and to be involved in car crashes than their female counterparts [6]. The factors associated with RTA's in the country are comparable to what one would expect in most countries, although a further breakdown of factors under 'other' categories is necessary since that particular category has over half the number of accidents.…”
Section: Road Traffic Accidentsmentioning
confidence: 69%
“…[6,15,16].Drivers were chosen to identify relevant factors that contribute to the traffic accidents in Abu Dhabi.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…15 Sabbour et al reported a number of common risky driving styles and behaviours, similar to the findings in this study, among medical students in Egypt. 20 These included driving at excessive speeds, driving without a licence, not wearing a seat belt and answering mobile phones while driving. 20 Similarly, a study from India revealed that 20% of medical students admitted to using hands-free mobile phones while driving and 68% revealed that they had surpassed speed limits on multiple occasions.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, Sabbour & Ibrahim 31 , in a study of 450 medical students using a self-administered questionnaire that focused on driving styles and behaviors and their association with road traffic accidents, found that speeding and not wearing a seatbelt and talking on the cell phone while driving were more prevalent among male drivers. Cell phone use while driving and speeding (among other factors) were significantly associated with medical students' involvement in car accidents.…”
Section: Speed Camerasmentioning
confidence: 99%